LAPORAN ANALISIS DESAIN ORGANISASI SEBAGAI DASAR REKOMENDASI MANAJEMEN STRATEGIS - Eri Sugiarto; Muhammad Arjalulwahid Aliyah; Affan Nur Fitrahman As Sidiq; Rony Edward Utama (Media Riset Bisnis Manajemen Akuntansi, 2026)
Organizational design is a fundamental aspect that determines the effectiveness and efficiency of both public and private institutions. This study aims to analyze the organizational design applied in the Siwalan District Government, PT Telkom Indonesia, and PT Pertamina Hulu Rokan (PHR), as well as to formulate strategic management recommendations to improve performance effectiveness. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation, then validated using source, method, and time triangulation. The results show that the Siwalan District Government has an appropriate structure according to regulations but faces challenges in coordination and centralization. PT Telkom Indonesia’s Human Capital Management Directorate effectively utilizes the SAP HCM system, although its use remains suboptimal due to limited user training. PT Pertamina Hulu Rokan applies the Five Star Model by Galbraith, yet still requires improvement in cross-divisional coordination and reward systems. Overall, effective organizational design is achieved through alignment among strategy, structure, process, people, and reward systems. Continuous evaluation and adaptation are essential to enhance organizational effectiveness and sustainability across sectors.Keywords: organizational design, performance effectiveness, public sector, strategic management, sustainability